The effect of age on pulmonary and muscle oxygenation kinetics following high-intensity interval exercise - Borges, N. R.; Reaburn, P. R.; Doering, T. M.; Argus, C. K.; Driller, M. W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Physiological measures of pulmonary and muscle oxygenation follow an exponential trends following exercise until reaching baseline values. A steeper exponential trend suggests faster post-exercise recovery. To date, no study has investigated the effect of age on off-transient pulmonary and muscle oxygenation kinetics following high-intensity interval exercise (HIIE) typical of training undertaken by both competitive endurance and sprint cyclists. Therefore, this study examined the effect of age on the off-transient pulmonary and muscle oxygenation kinetics in well-trained masters and young cyclists following HIIE. Methods: Pulmonary (V O2) and muscle oxygenation (Total Oxygenation Index [TOI] and change in deoxyhemoglobin concentration ( [HHb]) were monitored continuously in well-trained masters (n = 9, age: 55.6 ± 5.0 yr) and young (n = 8, age: 25.9 ± 3.0 yr) cyclists during HIIE and recovery. The HIIE consisted of 6 x 30 second intervals at 175% maximal aerobic power with 4.5 minutes rest between intervals. Following the HIIE, 20 minutes of passive supine rest was undertaken. The off-transient responses of V O2, TOI and [HHb] from the cessation of the HIIE were then modelled using a mono-exponential function. Results: The time constant ( ) of the V O2 response ( V O2) was significantly longer in the masters (mean ± SD; 217.49 ± 44.43 s) compared to young (169.69 ± 35.73 s) cyclists (P = 0.029). The amplitude of the V O2 response was also lower in masters (d = 0.69, moderate), although not significant (P = 0.18). A trend for a slowed TOI was found in the masters cyclists, however this was not found to be significant (P = 0.40, d = 0.42, small). Significant correlations were observed between TOI, and both V O2 (r = 0.49, P = 0.049) and [HHb] (r = 0.75, P < 0.001), and a non-significant moderate relationship was found between age and V O2 (r = 0.48, P = 0.05). Discussion: The significantly slowed V O2 suggests that masters athletes exhibit longer time for metabolic recovery following HIIE. Additionally, although no significant age-related differences for muscle re-oxygenation kinetics where observed a trend for a slower TOI during the recovery phase was found. The slowed pulmonary and muscle oxygenation kinetics may have a negative effect on repeat sprint performance in masters athletes and greater recovery periods between exercise bouts may be necessary to maintain power output.